Simulation of Series Active Power Filter for Harmonics Mitigation: Enhancing Power Quality through Series Active Power Filter Simulation (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Over the past few years, the enormous increase in the use of non-linear loads, arises many power quality issues like high current harmonics, voltage distortion and low power factor etc. on electrical grid (Swain, et. al., 2016). In this paper, a new robust controller design for HSAPF has been presented. The control design is established by sliding mode controller-2 that derives the equivalent control law. This control law is very much helpful for switching pattern generation. The robust- ness of the proposed controller has been verified by analyzing the performance under steady state as well as transient condition of the power system. With the application of this technique, the functionalities of the HSAPF are enhanced. From the obtained simulations as well as experimental results, the proposed HSAPF has been observed to provide efficient current as well as voltage harmonic mitigation, reference voltage tracking behavior, and reactive power compensation with dynamically varying load conditions.